2007
DOI: 10.1161/01.str.0000257966.32242.0b
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Application of 20-kHz Transcranial Ultrasound in an Embolic Middle Cerebral Artery Occlusion Model in Rats

Abstract: Background and Purpose-Therapeutic application of diagnostic ultrasound has been shown to improve recanalization rates in patients with acute cerebral vessel occlusion. There is experimental evidence that low-frequency ultrasound may be superior. This study was designed to evaluate the therapeutic efficacy and safety of low-frequency ultrasound in an embolic middle cerebral artery occlusion model in rats. A parameter setting was used that had not previously shown any side effects and interactions with healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…For example, 20-kHz continuous-wave ultrasound sonication with an intensity of 0.2 W/cm 2 causes hemorrhagic damage (including subarachnoid and intracerebral hemorrhage), massive edema, and increases the rate of animal death (15). Similar hemorrhages and edema were seen in a recent multicenter clinical study in which 300-kHz ultrasound was applied transcranially as a thrombolytic treatment (25,28).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…For example, 20-kHz continuous-wave ultrasound sonication with an intensity of 0.2 W/cm 2 causes hemorrhagic damage (including subarachnoid and intracerebral hemorrhage), massive edema, and increases the rate of animal death (15). Similar hemorrhages and edema were seen in a recent multicenter clinical study in which 300-kHz ultrasound was applied transcranially as a thrombolytic treatment (25,28).…”
Section: Discussionmentioning
confidence: 72%
“…The contrast agent is then measured directly, and drug delivery is determined based on its concentration on the contrast agent (12,13). The second method assesses therapeutic agent delivery to the brain more accurately, and SPIO nanoparticles have many advantages in this regard: (i) SPIO nanoparticles are biocompatible and can be degraded safely by macrophages/ microglia (14), whereas gadolinium leakage raises safety concerns related to neurotoxicity (15); (ii) SPIO nanoparticle surfaces can be modified to easily conjugate therapeutic agents (12,13); (iii) MRI techniques such as T 2 *-weighted imaging or transverse relaxation rate (R 2 ) maps can be used to quantify the iron concentration in tissues, making quantification of therapeutic agent delivery easier (12,13); (iv) SPIO nanoparticles have high spin-spin relaxivities and can generate high magnetic moments that can be actively manipulated by externally applied magnets, making them suitable for use with magnetic targeting (16,17). The above advantages makes the SPIO nanoparticles has the potential to serve a ''thernostic'' agent, which means that the diagnostic and therapeutic functions can be concurrently provided during drug-delivering process.…”
mentioning
confidence: 99%
“…Furthermore, a recent study demonstrated that TUS (20 kHz, continuous wave), even at low intensity (0.2 W/cm 2 ), resulted in a significantly higher death rate when applied to a rat MCA stroke model. 24 These results indicate that low-frequency TUS has the potential for brain damage, depending on the ultrasound conditions used. However, it should be pointed out that the mechanical index (MI) is an important indicator that can be used to estimate the potential for mechanical effects arising from ultrasound.…”
Section: Discussionmentioning
confidence: 89%
“…Using an optical technique, Azuma et al (2005) observed similar acoustic patterns attributed to standing waves. We postulate that hemorrhages noted clinically in the contralateral, in clinical trials of ultrasound enhanced thrombolysis, might be due to such standing waves (Daffertshofer et al 2005;Reinhard et al 2006;Wilhelm-Schwenkmezger et al 2007). …”
Section: Discussionmentioning
confidence: 98%